Sumithion usage in aquaculture: benefit or forfeit?. (29th March 2021) - Shahjahan, Md; Islam, SM Majharul; Bablee, Alif Layla; Siddik, Muhammad A.B.; Fotedar, Ravi
Abstract: Sumithion is an organophosphate insecticide, extensively used to remove tiger bug from aquaculture ponds prior to the release of fish larvae. Its usage in aquaculture may initially assist in insect eradication; however, the harmful effects of sumithion may surpass the beneficial effects and may be alarming for the farmed fish and other aquatic organisms. This study summarizes the consequential effects of sumithion on the natural productivity in aquaculture ponds, and early development, physiological response, and reproductive functions of the farmed fish. Studies have found that sumithion adversely affects the natural production of phytoplankton, zooplankton and benthos, and reduces the hatching success with increased mortality, and morphological alterations in fish embryos and larvae. Fish haematological and biochemical alterations are also reported to be induced by the exposure to sumithion, as are variety of histopathological alterations and reproductive dysfunctions in exposed fish. Overall, this study is the first comprehensive overview of any insecticide which may advance our understanding of the rational and restricted use of insecticide in aquaculture operations.